Hubungan Kesegaran Jasmani terhadap Prestasi Hasil Belajar Siswa Sekolah Menengah Atas - Hidayat, Joni; Porja Daryanto, Zusyah; Duli Agus Lauh, Whalsen (Indonesian Journal of Physical Education and Sport Science, 2023)
Purpose of Study. This research was aimed to describe: (1) The physical degree of students in XI class of SMA Negeri 3 Sukadana in Kayong Utara Regency; (2) The student’s achievement in XI class of SMA Negeri 3 Sukadana in Kayong Utara Regency; (3) The correlation between physical fitness toward student’s learning performance in XI class of  SMA Negeri 3 Sukadana in Kayong Utara Regency. Material and Method. The research method used was a descriptive correlative study wita h quantitative approach. The technique of data collection was by using measurement and document study. The instruments used were the test of Tes Kebugaran Jasmani Indonesia (TKJI) to know the student’s physical degree, where the test was intended to 16-19 years old students. Meanwhile, to get the information related to student’s achievement, the instrument used was the students achievement document. The sample of the study were XI class students of SMA Negeri 3 Sukadana in Kayong Utara Regency, which consist of 36 students. The technique of data analysis by using the formula if product moment correlation. Results. (1) The average fitness of the students physics in this class is 13.4, which is categorize as poor; (2) The average score of the students learning performance in physical education is 80.1, which was categorized as good; (3) In order to find out whether there is correlation or not between the students physical fitness and their physical achievement, the hypothesis was tested by using product moment correlation with rvalue = -0,936 < rtabel  = 0,32. Conclusion. Based on the data analysis it can be concluded that there is no significant positive correlation between the student’s physical fitness and their learning performance of XI class students in SMA Negeri 3 Sukadana in Kayong Utara Regency.